2001
DOI: 10.1021/ic000553a
|View full text |Cite
|
Sign up to set email alerts
|

Azametallacycles from Ag(I)- or Cu(II)-Promoted Coupling Reactions of Dialkylcyanamides with Oximes at Pt(II)

Abstract: The dialkylcyanamide complexes cis-[PtCl(NCNR(2))(PPh(3))(2)][BF(4)] 1 and cis-[Pt(NCNR(2))(2)(PPh(3))(2)][BF(4)](2) 2 (R = Me or Et) have been prepared by treatment of a CH(2)Cl(2) solution of cis-[PtCl(2)(PPh(3))(2)] with the appropriate dialkylcyanamide and one or two equivalents of Ag[BF(4)], respectively. Compounds 2 can also be obtained from 1 by a similar procedure. Their reaction with oximes, HON=CR'R' ' (R'R' ' = Me(2) or C(4)H(8)), in CH(2)Cl(2) and in the presence of Ag[BF(4)] or Cu(CH(3)COO)(2), le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 58 publications
9
54
0
Order By: Relevance
“…It was recognized earlier that in many instances ligated Alk 2 NCN compounds exhibit different behavior from the coordinated conventional nitriles RCN. These differences were recognized not only at the quantitative,17f,30 but also at the qualitative level2e,3a,3b,3e when conventional nitrile and dialkylcyanamide ligands react with the same reagent in different ways to give, consequently, different products. The distinctions in the reaction routes are accounted for by a special role of the NR 2 group in dialkylcyanamides.…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized earlier that in many instances ligated Alk 2 NCN compounds exhibit different behavior from the coordinated conventional nitriles RCN. These differences were recognized not only at the quantitative,17f,30 but also at the qualitative level2e,3a,3b,3e when conventional nitrile and dialkylcyanamide ligands react with the same reagent in different ways to give, consequently, different products. The distinctions in the reaction routes are accounted for by a special role of the NR 2 group in dialkylcyanamides.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, imines with very close structural characteristics being ligated to a metal center can exhibit even the opposite reactivity modes, for example, stabilization vs activation toward hydrolysis. 2 Recently we (see reviews 3 ) and others 4 found explicit evidence that platinum group metals, [5][6][7][8][9] rhenium, 10 gold, 11a,b or silver 11c centers provide enormous stabilization of the potentially unstable imines RR′CdNH, and these ligands can be "stored" without changes in the coordinated form under normal conditions for a prolonged time. Moreover, it appears that the formation of imines is one of the major driving forces for some reactions, e.g., condensation of complexed ammonia with ketones, 11 reductions of oximes, 12 oxidative dehydration of amines (e.g., at Fe, 13 Ru, 14,15 Os, 16 Re, 17 and Pt 18 centers), and nucleophilic additions to metal-bound nitriles.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been observed that some push-pull nitrilecontaining complexes, in particular dialkylcyanamide metal species, display unusual reactivity patterns unknown for conventional RCN compounds (Bokach et al, 2003;Cunha et al, 2002;Ferreira et al, 2001;Guedes da Silva et al, 1997;Pombeiro et al, 1989). This difference, in view of our general interest in the reactions of metal-activated nitriles (Kukushkin et al, 2002;Kukushkin et al, 2005;Bokach et al, 2005), prompted us to verify some structural differences between push-pull and conventional nitrile species ligated to a Pt II centre.…”
mentioning
confidence: 99%